A Comparative Study of Methotrexate Alone and Methotrexate with Hydroxychloroquine in Rheumatoid Arthritis Patients in A Tertiary Care Teaching Hospital - Dr. Pooja Agrawal; Dr. Virendra Kushwaha; Dr. Vipul Shukla; Dr. Praganesh Kumar; Dr. Amit Kumar; Dr. Himanshu Sharma (International Journal of Pharma and Bio Sciences, 2023)
Rheumatoid arthritis (RA) is a chronic, progressive autoimmune disease associated with polyarthritis and dysfunction of joints. Early diagnosis and treatment may affect disease outcomes even to a remission state. If not treated properly, it may increase morbidity and mortality due to extra-articular manifestations. No clear guidelines are available regarding the use of various Disease Modifying Anti Rheumatic Drugs and other immunosuppressive drugs in RA. Physicians have also used hydroxychloroquine (HCQS) due to its anti-inflammatory property. We aim to compare the effectiveness and safety profile of Methotrexate (MTX) monotherapy and HCQS in RA patients. Patients of RA attending Orthopaedic OPD at GSVM Medical College, Kanpur, are included and followed up for 6 months. Patients of Group A are treated with MTX alone, while Group B is treated with a combination of MTX plus HCQS. The effectiveness of the treatment is evaluated by improvement in the DAS28 scale at each follow-up visit. Drug safety profiles are assessed by Adverse drug reactions reported by patients and their causality assessment per Naranjo's probability score. In our study, 61 patients are included. The mean age is 49 years, while male to female ratio is 1:5. Improvement in the DAS28 score in the combination therapy group is significant (p value<0.05). Both groups had adverse events associated with their treatment. Still, none of the Adverse Drug Reactions was definite as per Naranjo's probability score, and a maximum number of Adverse Drug Reactions were non-serious. Our study concluded that combination therapy (MTX plus HCQS) provides better disease control. Combination therapy shows an almost similar safety profile; the frequency of adverse events was also similar to MTX alone. HCQS is a cost-effective drug easily available in India, so it would be better to use combination therapy in RA to control the disease.